Answer :
Answer:
x = 30.
Step-by-step explanation:
8x - 3(2x - 4) = 3(x - 6)
8x - 3*2x + - 3*-4 = 3*x + 3 * -6
8x - 6x + 12 = 3x - 18
2x + 12 = 3x - 18
2x - 3x + 12 = 3x - 3x - 18
-x + 12 = -18
-x + 12 - 12 = -18 - 12
-x = -33
-x/-1 = -30/-1
x = 30.
Answer:
[tex]x=30[/tex]
Step-by-step explanation:
[tex]8x-3\left(2x-4\right)=3\left(x-6\right)[/tex]
First, we will expand [tex]-3\left(2x-4\right)[/tex] by applying the distributive property:
[tex]-3\times \:2x-\left(-3\right)\times \:4[/tex]
** [tex]-\left(-a\right)=a[/tex]
[tex]-6x+12[/tex]
[tex]8x-6x+12=3\left(x-6\right)[/tex]
Expand, [tex]3\left(x-6\right):[/tex]
[tex]3x-3\times \:6[/tex]
[tex]3x-18[/tex]
[tex]2x+12=3x-18[/tex]
Subtract 12 from both sides:
[tex]2x+12-12=3x-18-12[/tex]
[tex]2x=3x-30[/tex]
Subtract 3x from both sides:
[tex]2x-3x=3x-30-3x[/tex]
[tex]-x=-30[/tex]
Divide both sides by -1:
[tex]\frac{-x}{-1}=\frac{-30}{-1}[/tex]
[tex]x=30[/tex]
________________________